For a decolonial teacher’s education in Brazil - Medeiros, Bianca Sgai Franco (The ESPecialist, 2025)
This article presents an excerpt from the research entitled “Decolonial Education of Educators: Engaged Multiliteracy in an Extension Project” (Medeiros, 2023). Situated within the field of Critical Applied Linguistics (MOITA LOPES, 2006) and based on Socio-Historical-Cultural Theory (VYGOTSKY, 2001; LEONTIEV, 2014), the research results from a qualitative-interpretative multimodal analysis of part of the course “Engaged Multiliteracies: Curriculum as (Trans)formation.” Free of charge and offered to education professionals, undergraduate students, and Basic Education students through the Extension Project “Brincadas: The Viable Unheard of in Times of Crisis,” which took place in the second semester of 2021. This study mainly focuses on investigating the possibility of a decolonial path (MIGNOLO; WALSH, 2018) for the continuous education of educators by working with techniques from the Theatre of the Oppressed (BOAL, 1970) within part of a proposal for Engaged Multiliteracy (LIBERALI, 2022). Specifically, it provides an analysis of a proposition in Reality Immersion, assessing the engagement of the participants in a decolonial stance of the individuals involved. Therefore, this article is believed to facilitate reflection on the critical education of educators within its broader context in Brazil, through the multimodal interpretation of the data. It becomes evident that play in Engaged Multiliteracy serves as a powerful tool for engaging individuals in real issues of injustice, and that a planning process aimed at involving participants in the learning process allows for the development of transformative agency concerning the highlighted injustices. The need for new pedagogical practices that enable a rethinking of the education of these professionals was noted, envisioning more critically collaborative individuals who dare to exercise their transformative agency (VIANNA and STETSENKO, 2011) in the diverse and different educational contexts in which they operate, aiming for the possibility of the viable unprecedented (FREIRE, 1970) from an intercultural perspective (CANDAU, 2008) and decolonial stance in favor of social, cognitive, curricular, ecological, and epistemic justice.